Novel Modality in Heart Failure Treatment - Alexander Edo Tondas (Arkus, 2019)
Heart failure is a condition when the heart is unable to meet the metabolic demands of human body. Apart from the symptoms that impair the patient’s life, heart failure also carries a higher risk of mortality and consequently a higher economic burden due to hospitalization. As the disease progresses, the management will become more complex, and shifts from drugs to devices, to prevent cardiac transplant as the final frontier in heart failure therapy. In the industrial revolution era, 3D printing and bioprinting has emerged as a novel modality in dealing with heart failure pathophysiology.